SISTEM INFORMASI PENJUALAN BUKU BEKAS DI KOTA BANDAR LAMPUNG BERBASIS WEB - Machudor Yusman; Bambang Hermanto; Ibnu Rizaldi (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
This study aims to create an information system that functions to sell used books in the city of Bandar Lampung. Currently the used book sales system still relies on media interaction with direct consumers and is still centered on a particular location. By creating a web-based used book sales information system in the city of Bandar Lampung, it can facilitate customer transactions in purchasing used books online. In this research the system design uses UML (Unifield Modeling Language), PHP (Hypertext Preprocessor) programming language, MYSOL as a database and using Windows as an operating system. Information systems are created by applying the Extreme Programming Method to determine the steps in making a system. System functional testing uses the Black Box Testing method in the functional test scenario. Accuracy testing uses 20 test cases that exist in the information system, then performed related to the system output with actual events. From the test results using 20 test cases, the results obtained are in accordance with the system output so that the test results are categorized as very good.